Role of Health Insurance Policies in Access to Healthcare Services in Bangladesh - Haque, Samira (Journal of Public Policy and Administration, 2024)
Purpose: To aim of the study was to analyze the role of health insurance policies in access to healthcare services in Bangladesh. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The role of health insurance policies in Bangladesh is crucial in improving access to healthcare services, particularly for low-income populations. Health insurance has been found to reduce the financial barriers to accessing care, leading to increased utilization of essential health services. However, challenges such as limited coverage, awareness, and administrative inefficiencies persist, hindering the full potential of these policies. Expanding and refining health insurance schemes could significantly enhance healthcare accessibility and reduce out-of-pocket expenditures, ultimately contributing to better health outcomes across the country. Unique Contribution to Theory, Practice and Policy: The health belief model (HBM), the theory of planned behavior (TPB) & Andersen’s behavioral model of health services may be used to anchor future studies on the role of health insurance policies in access to healthcare services in Bangladesh. Health insurance providers should develop targeted outreach and education programs to inform underserved populations about available health insurance options and their benefits. Policymakers should consider implementing universal health insurance coverage mandates to ensure that all individuals, regardless of socioeconomic status, have access to healthcare services.